Antibiotics detected in urines and adipogenesis in school children. (April 2016) - Wang, Hexing; Wang, Na; Wang, Bin; Fang, Hong; Fu, Chaowei; Tang, Chuanxi; Jiang, Feng; Zhou, Ying; He, Gengsheng; Zhao, Qi; Chen, Yue; Jiang, Qingwu
Abstract: Background: Although antibiotic use during early life has been demonstrated to be related to the altered adipogenesis in later life, limited data are available for the effect of antibiotic exposure in school children on adiposity from various sources, including from the use or contaminated food or drinking water. Objective: To explore the association between the internal exposure of antibiotics from various sources and adipogenesis in school children using the biomonitoring of urinary antibiotics. Methods: After 586 school children aged 8–11 years were selected from Shanghai in 2013, total urinary concentrations (free and conjugated) of 21 common antibiotics from six categories (macrolides, β-lactams, tetracyclines, fluoroquinolones, sulfonamides, and phenicols), including five human antibiotics (HAs), two antibiotics preferred as HA, four veterinary antibiotics (VAs), and ten antibiotics preferred as VA, were measured by ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry. Creatinine-corrected urinary concentrations of antibiotics were used to assess their exposure. Overweight or obesity was determined by the body mass index or waist circumference-based criteria deriving from national data. Results: All 21 antibiotics were found in urines with the overall detection frequency of 79.6%. The multinomial logistic regression analyses showed the significant associations of overweight and obesity with the exposure to VAs and antibiotics preferred as VA, but not with HAs or antibiotics preferred as HA. After adjusted for a number of obesity-relevant variables, the odds ratios (95% confidence interval) of BMI-based obesity risk of tertiles 2 and 3 of urinary concentrations relative to tertile 1 were respectively 2.54 (1.27, 5.07) and 2.92 (1.45, 5.87) for florfenicol, 0.57 (0.12, 2.63) and 3.63 (1.41, 9.32) for trimethoprim, and 3.00 (1.56, 5.76) and 1.99 (0.99, 4.01) for sum of veterinary antibiotics. Similar results were found when the outcome used WC-based obesity risk. The associations were sex related and mainly observed in boys. Conclusions: Some types of antibiotic exposure, which were mainly from food or drinking water, were associated with an increased risk of obesity in school children. Due to the cross-sectional design, more longitudinal and experimental studies are warranted to further test these findings. Highlights: Urinary antibiotics were used to assess their internal exposure from various sources. Some antibiotic exposure was associated with increased adipogenesis in children. The association was found in veterinary antibiotics or antibiotics preferred as VA. The long-term exposure to low-dose antibiotics may be an important exposure mode. The significant associations differed by sex and mainly observed in boys.